Identification and characterization of mixed infections of Chlamydia trachomatis via high-throughput sequencing - Zhao, Jianhui; Shui, Jingwei; Luo, Lipei; Ao, Cailing; Lin, Hongqing; Liang, Yuanhao; Wang, Li; Wang, Haiying; Chen, Hongliang; Tang, Shixing (Frontiers in Microbiology, 2022)
Precise genotyping is necessary to understand epidemiology and clinical manifestations of Chlamydia trachomatis infection with different genotypes. Next-generation high-throughput sequencing (NGHTS) has opened new frontiers in microbial genotyping, but has been clinically characterized in only a few settings. This study aimed to determine C. trachomatis genotypes in particular mixed-genotype infections and their association with clinical manifestations and to characterize the sensitivity and accuracy of NGHTS. Cervical specimens were collected from 8,087 subjects from physical examination center (PEC), assisted reproductive technology center (ART) and gynecology clinics (GC) of Chenzhou Hospital of China. The overall prevalence of C. trachomatis was 3.8% (311/8087) whereas a prevalence of 2.8, 3.7 and 4.8% was found in PEC, ART and GC, respectively. The most frequent three C. trachomatis genotypes were E (27.4%, 83/303), F (21.5%, 65/303) and J (18.2%, 55/303). Moreover, NGHTS identified 20 (6.6%, 20/303) mixed-genotype infections of C. trachomatis. Genotype G was more often observed in the subjects with pelvic inflammatory disease than genotype E (adjusted OR = 3.61, 95%CI, 1.02–12.8, p = 0.046). Mixed-genotype infection was associated with severe vaginal cleanliness (degree IV) with an adjusted OR of 5.17 (95%CI 1.03–25.9, p = 0.046) whereas mixed-genotype infection with large proportion of minor genotypes was associated with cervical squamous intraepithelial lesion (SIL) with an adjusted OR of 5.51 (95%CI 1.17–26.01, p = 0.031). Our results indicated that NGHTS is a feasible tool to identity C. trachomatis mixed-genotype infections, which may be associated with worse vaginal cleanliness and cervical SIL.